1992
DOI: 10.1159/000126188
|View full text |Cite
|
Sign up to set email alerts
|

Type II Corticosteroid Receptor-Like Immunoreactivity in the Rat Cerebellar Cortex: Differential Regulation by Corticosterone

Abstract: Type II corticosteroid receptor-like immunoreactivity (type Il-ir) was localized at the light- and electron-microscopic levels in the rat cerebellar cortex using BUGR2 monoclonal antibody. In intact rats, type II-ir was observed in the nuclei of basket, stellate, Golgi and Purkinje cells. After 1 week of adrenalectomy, type IIir was barely resolvable in basket, stellate, Golgi and most Purkinje cells. Vermal Purkinje cells showed intense nuclear and cytoplasmic type II-ir. After 4 weeks of adrenalectomy, type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Furthermore it has been suggested that acute or chronic stress might lead to earlier onset or worsening of the motor symptoms of PD (Smith, Castro, & Zigmond, 2002;Treves, Rabey & Korczyn, 1990). The high density of glucocorticoid receptors in some brain areas linked to the motor control, such as the cerebellum, basal ganglia and motor cortex, render these areas susceptible to the effects of stress (Ahima & Harlan, 1990;Ahima, Tagoe, & Harlan, 1991). In addition, it has been demonstrated that oxidative stress caused by immobilization stress selectively damages the nigrostriatal dopaminergic system (Kim, Choi, Chang, Kim, & Hwang, 2005), indicating that the dopaminergic system is particularly susceptible to the effects of stress (Izzo, Sanna, & Koob, 2005;Pani, Porcella, & Gessa, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore it has been suggested that acute or chronic stress might lead to earlier onset or worsening of the motor symptoms of PD (Smith, Castro, & Zigmond, 2002;Treves, Rabey & Korczyn, 1990). The high density of glucocorticoid receptors in some brain areas linked to the motor control, such as the cerebellum, basal ganglia and motor cortex, render these areas susceptible to the effects of stress (Ahima & Harlan, 1990;Ahima, Tagoe, & Harlan, 1991). In addition, it has been demonstrated that oxidative stress caused by immobilization stress selectively damages the nigrostriatal dopaminergic system (Kim, Choi, Chang, Kim, & Hwang, 2005), indicating that the dopaminergic system is particularly susceptible to the effects of stress (Izzo, Sanna, & Koob, 2005;Pani, Porcella, & Gessa, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies have confirmed the presence of GR in the motor cortex, basal ganglia, and cerebellum [15,16], thus rendering these areas sensitive to glucocorticoid actions. By contrast, MR in the motor system appears to be restricted to cortical layers II, III and V [39].…”
Section: Discussionmentioning
confidence: 99%
“…Although in comparatively lower density than in limbic regions, MR and GR have also been detected in regions participating in motor control, including the motor cortex, basal ganglia, cerebellum, and spinal cord [15,16,17,18,19], suggesting that corticosteroids are important modulators of motor function. Indeed, systemic administration of CORT or stress disturbs skilled and non-skilled movement at both acute and long-term intervals [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, an increasing number of data suggest that they could be an important risk factor in the pathogenesis. GR density is not equal in all brain structures, and interestingly is higher in regions such as the motor cortex, basal ganglia and cerebellum, which are involved in motor control [25,26] . This makes these areas more susceptible to the effects of stress in both human [27] and rat [28,29] .…”
Section: Chronic Stress Is a Risk Factor For The Development Of Neuromentioning
confidence: 99%